TECHNIQUES FOR UTILIZING ORGANIC WASTE INTO BIO-COMPOST - Indah Nuzulul Rohmah; Inayah Fitri; Nur Maulidah (Jurnal Matematika dan Sains (JMS), 2022)
Utilization of fruit peel organic waste into bio-compost is one of the countermeasures of the harmful impacts on health or the environment. Therefore, the technique of making compost with the basic ingredients of organic waste is anaerobic and physical analysis of the composting results is carried out. This research was conducted in December 2021 – March 2022 at the traditional markets of Sekaran Village and Jangkungsumo Village. This research is classified as exploratory using purposive sampling technique. The results obtained are that in the composting process there are several stages including composting, fermentation and compost burial. On the physical characteristics that have been analyzed in compost made from organic waste, the fruit skin has a blackish color like soil, then has a dense and crumbly texture and smells of earth. This has met the compost standards that have been determined.